Suppression of large t antigen-stimulated CD4+CD25+ and CD8+IFN-γ+ T cells is strongly associated with low level BK viremia in kidney transplant recipients - Saisorn, Wilasinee; Wuttiputhanun, Thunyatorn; Vanichanan, Jakapat; Jutivorakool, Kamonwan; Townamchai, Natavudh; Avihingsanon, Yingyos; Leelahavanichkul, Asada; Udomkarnjananun, Suwasin (Frontiers in Medicine, 2025)
BackgroundBK polyomavirus (BKPyV) infection following kidney transplantation results from over-suppression of cellular immunity. Currently, there is no established, clinically applicable immunological assay that comprehensively monitors cellular immune responses against BKPyV, incorporating both cytokine production and T cell activation markers. Our study aimed to comprehensively assess both cytokine production and surface activation markers to differentiate kidney transplant recipients (KTR) with low-level (<3,000 copies/mL) BKPyV viremia from those without viremia.MethodsThirty-six participants were enrolled, comprising KTR with (BK) and without BKPyV viremia (nBK), alongside healthy controls (HC). Peripheral blood mononuclear cells (PBMC) were stimulated using BKPyV viral capsid protein-1 (VP1) or large-T-antigen (LTA), with and without CD28/CD49d co-stimulatory antibodies. Outcomes included expression of IL-2, IFN-γ, TNF-α, CD25, CD134, CD137, and CD154. Candidate markers were evaluated by calculating the area under the receiver operating characteristic curve (AUROC) for diagnosing BKPyV viremia.ResultsVP1- or LTA-stimulated CD4+ and CD8+ T cells showed optimal discriminatory power between BK and nBK groups when co-stimulated with CD28/CD49d. VP1-stimulated CD4+ cells differed significantly between groups in IL-2, TNF-α, CD25, and CD137, while CD8+ cells differed significantly in IFN-γ and CD25. LTA-stimulated CD4+ cells showed significant differences in TNF-α and CD25, and CD8+ cells differed significantly in IFN-γ and CD25. LTA-stimulated CD4+CD25+ and CD8+IFN-γ+ cells provided significant AUROC values (0.823, 95%CI 0.657–0.989, p = 0.030; and 0.833, 95%CI 0.678–0.989, p = 0.028, respectively) at a cutoff of > 0.2% positive cells.ConclusionLTA-stimulated CD4+CD25+ and CD8+IFN-γ+ T cells differentiated KTR with and without low-level BKPyV viremia, representing promising markers for early clinical diagnostics and future studies.